Injection Site Reactions in the Federal Adverse Event Reporting System (FAERS) Post-Marketing Database Vary Among Biologics Approved to Treat Moderate-To-Severe Psoriasis - Grace, Elsie (Dermatol Ther (Heidelb), 2019)
INTRODUCTION: Biologics used to treat moderate-to-severe plaque psoriasis may cause injection site reactions (ISRs) characterized by erythema, edema, itch, and sometimes pain. The Federal Adverse Event Reporting System (FAERS) is a repository of spontaneous post-marketing reports of adverse events (AEs) that are reported to the US Food and Drug Administration (FDA). Our objective was to perform a pharmacovigilance analysis of FAERS reports of ISRs associated with the use of subcutaneously administered biologic products approved to treat moderate-to-severe plaque psoriasis. METHODS: The products included in our assessment were adalimumab, etanercept, ixekizumab, secukinumab, and ustekinumab. Reports from the date of US approval for each biologic as treatment for plaque psoriasis through 2 years were included using the search term “injection site.” RESULTS: The results show that the FAERS database contained reports of ISRs for all of the included biologics during the 2 years following FDA approval. The most common reports on ISRs were on pain, irritation, and erythema for adalimumab; reaction, pain, and erythema for etanercept; erythema, pain, and reaction for ixekizumab; bruising, pain, hemorrhage for secukinumab; and pain, induration, and swelling for ustekinumab. FAERS does not include data on total patient exposure; therefore, ISR rates could not be calculated. CONCLUSIONS: Specific ISRs varied among the biologic therapies assessed. The findings presented could be helpful when patients consider switching therapies due to ISRs. FUNDING: Eli Lilly and Company.